Modern approaches to stress testing central banks and financial systems: lessons learned from the crisis - Lobanov, Alexey (Henry Stewart Talks, 2012)
Risk profile of central banks, Risk management issues at central banks, Objectives for stress testing at financial firms, central banks and regulators, Stress testing on portfolio level, Pre-crisis recommendations for stress testing, Innovative stress testing methodologies, Stress testing financial systems, Bottom-up and top-down approaches to macro stress testing, Examples of top-down stress testing, Case study: FSAP scenarios and real dimensions of crisis in Russia in 2008-09, Select principles for sound stress testing, Reverse stress testing, Open issues and challenges